2018
DOI: 10.1175/jhm-d-18-0006.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Atmospheric Rivers on Precipitation in Southern South America

Abstract: This study quantifies the impact of atmospheric rivers (ARs) on precipitation in southern South America. An AR detection algorithm was developed based on integrated water vapor transport (IVT) from 6-hourly CFSR reanalysis data over a 16-yr period (2001–16). AR landfalls were linked to precipitation using a comprehensive observing network that spanned large variations in terrain along and across the Andes from 27° to 55°S, including some sites with hourly data. Along the Pacific (west) coast, AR landfalls are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 41 publications
8
150
1
Order By: Relevance
“…This method performs well when the AR has an elongated shape but has difficulties when the AR is sharply curved or otherwise complicated in structure because the slicing may not be optimally placed/oriented in these cases. Such difficulties were also noted in Viale et al () where a similar method was used for finding the AR axis, and, in dealing with the issue, candidate ARs with complicated structure were discarded. In the current algorithm, the AR axis is identified by tapping the previously unused information in IVT direction.…”
Section: Data and Methodsologymentioning
confidence: 93%
“…This method performs well when the AR has an elongated shape but has difficulties when the AR is sharply curved or otherwise complicated in structure because the slicing may not be optimally placed/oriented in these cases. Such difficulties were also noted in Viale et al () where a similar method was used for finding the AR axis, and, in dealing with the issue, candidate ARs with complicated structure were discarded. In the current algorithm, the AR axis is identified by tapping the previously unused information in IVT direction.…”
Section: Data and Methodsologymentioning
confidence: 93%
“…For southern California, Harris and Carvalho () note that conditions prior to AR making landfall differ from those for the Pacific Northwest with the intraseasonal to interannual variability in AR frequency conditioned on phases of modes of climate variability such as ENSO and the Madden Julian Oscillation as Debbage et al () found for AR over the southeast of the United States. For South America, AR landfalls are most frequent over the latitudinal range 38°S–50°S, occurring on average 35–40 days per year (Viale, Valenzuela, Garreaud, & Ralph, ). North and south of this band AR decrease rapidly as they do east of the Andes.…”
Section: Atmospheric Riversmentioning
confidence: 99%
“…North and south of this band AR decrease rapidly as they do east of the Andes. Contributing 45–60% of the annual precipitation in subtropical Chile and 40–55% along the midlatitude west coast, AR for this region exceed the importance for annual precipitation in the Pacific Northwest, most likely due to the severe orographic forcing, achieved under the influence of the Andes (Viale et al, ).…”
Section: Atmospheric Riversmentioning
confidence: 99%
See 1 more Smart Citation
“…Landslides in the Western U.S. are also more likely to occur in conjunction with ARs on lands affected by wildfires [12]. The importance of ARs has been documented in a variety of climate zones, and across the globe (e.g., References [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]).…”
Section: Introductionmentioning
confidence: 99%